Corticomuscular Coherence Modulation With the Pattern of Finger Force Coordination - Wu, Xiaoying; Li, Weina; Shen, Shan; Zheng, Xiaolin; Zhang, Yang; Hou, Wensheng (IEEE transactions on neural systems and rehabilitation engineering, 2013)
We assess the corticomuscular coherence (CMC) of the contralateral primary motor cortex and the hand muscles during a finger force-tracking task and explore whether the pattern of finger coordination has an impact on the CMC level. Six healthy subjects (three men and three women) were recruited to conduct the force-tracking tasks comprising two finger patterns, i.e., natural combination of index and middle fingers and unnatural combination of index and middle fingers (i.e., simultaneously producing equal force strength in index and middle finger). During the conducting of the tasks with right index and middle finger, MEG and sEMG signals were recorded from left primary motor cortex (M1) and right flexor digitorum superficialis (FDS), respectively; the contralateral CMC was calculated to assess the neuromuscular interaction. Finger force-tracking tasks of Common-IM only induce beta-band CMC, whereas Uncommon-IM tasks produce CMC in both beta and low-gamma band. Compared to the force-tracking tasks of Common-IM, the Uncommon-IM task is associated with the most intensive contralateral CMC. Our study demonstrated that the pattern of finger coordination had significant impact on the CMC between the contralateral M1 and hand muscles, and more corticomuscular interaction was necessary for unnaturally coordinated finger activities to regulate the fixed neural drive of hand muscles.